Studi Kesesuaian Pantai Jemeluk Sebagai Kawasan Wisata Bahari Kabupaten Karangasem, Provinsi Bali - Setiawan, I Gusti agung bayu; Dharma, I Gusti Bagus Sila; Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences; Vol 9 No 1 (2023), 2023)
Jemeluk Beach is located in Purwakerti village, district of Abang, Karangasem regency. Jemeluk Beach is a developing tourism sector in Karangasem, which has the potential for coral reefs and various types of reef fish. Jemeluk Beach has snorkeling and diving tourism activities to develop its potential. With this is potential, s necessary to conduct research to analyze and develop suitable snorkeling and diving tours in the waters of Jemeluk Beach. This research was conducted at Jemeluk Beach, there are 6 stations in the research sampling. Collecting coral reef data using the Underwater Photo Transect method. Determination the level of the suitability of the area as a diving and snorkeling tourism spot using a matrix of area suitability analysis that considered the parameters of ecological conditions and water quality conditions using three parameters. The result showed that coral reef cover value ranged from 35,78% - 81,0%, the types of lifeform found ranged from 8 - 10 species, the water transparency value ranged from 57,78 - 82,22%, the water depth at stations 1, 2 and 3 is 3 - 4 m, station 4 is 10 - 15 m, and stations 5 and 6 are 5 - 10 m, current speed ranged from 11-15 cm/s, and the tourism suitability index (IKW) for the snorkeling and diving category at Jemeluk beach is included in the S2 category, which is conditional.